1986
DOI: 10.1128/iai.53.3.498-504.1986
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal factors in vaginal candidiasis in rats

Abstract: The hormonal status of rats affected vaginal infection with Candida albicans. Four hours after infection viable counts were higher and germ tubes were longer in those animals in estrous than in other animals. However, the infection was not maintained with the change in epithelial cell type which occurred as part of the estrous cycle. Estrogen dosing following ovariectomy predisposed toward infection, while progesterone dosing did not. In rats injected with progesterone, germ tube clumping was seen, leukocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…6 Estrogen has been shown to promote C. albicans adhesion by inducing hyphal growth. 7,8 Additionally, estriols, pregnanediols, pregnanetrials and estradiols have been shown to increase germination of C. albicans. 9,10 The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Estrogen has been shown to promote C. albicans adhesion by inducing hyphal growth. 7,8 Additionally, estriols, pregnanediols, pregnanetrials and estradiols have been shown to increase germination of C. albicans. 9,10 The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization. 8,11,12 Several investigators have used estrogen in conjunction with C. albicans vaginal inoculation to construct animal models of persistent VC; among these models is the estrogen-dependent VC (EDVC) murine model. [13][14][15] This model has proved to be useful in evaluating the various aspects of pathogenesis of VC as VC in the absence of estrogen treatment in the murine system is transient and only lasts for few days.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations the data reported here are, to our knowledge, the first description of a successful rat experimental vaginal infection with the yeast Candida parapsilosis. This infection was seen not to differ in number of vaginal CFU from that caused by a vaginitis isolate of C. albicans, and estrogen administration was, as for C. albicans-rat vaginitis [11], essential for the maintenance of infection. Yeast viable counts in the vaginal fluid of our C. albicans-positive control experiments were comparable to those measured by others in a similar model of experimental rat vaginitis given by a fresh vaginal isolate of C. albicans [11].…”
Section: Discussionmentioning
confidence: 78%
“…This infection was seen not to differ in number of vaginal CFU from that caused by a vaginitis isolate of C. albicans, and estrogen administration was, as for C. albicans-rat vaginitis [11], essential for the maintenance of infection. Yeast viable counts in the vaginal fluid of our C. albicans-positive control experiments were comparable to those measured by others in a similar model of experimental rat vaginitis given by a fresh vaginal isolate of C. albicans [11]. Two other isolates of C. parapsilosis were unable to cause a prolonged infection, and it is of interest that one of them was isolated from the vagina of an asymptomatic subject.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation